Large scale parallel network simulation - Lawless, Eoin (Trinity College (Dublin, Ireland). School of Mathematics, 2004)
Simulation is one of the primary tools used in studying computer networks. However the difficulties of simulating a network grow with its size. With the hardware resources currently available it is not feasible to simulate Internet scale networks using conventional techniques. The sheer size of the Internet prohibits its detailed simulation by, for example, discrete event simulation. The complexity of its imderlying protocols has hindered the development of analytic models. The problem has been attacked on two fronts. One approach involves increasing computational power by harnessing many processors at once, typically using the methods of parallel discrete event simulation. The other approach advocates increasing the abstraction of a model, accepting that some approximation will be introduced into the model, but seeking to minimise its effect on behaviour of interest.
Keywords: Mathematics, Ph.D.; Ph.D. Trinity College Dublin